Assassin's Revenge - Larsen, Ward (Forge, 2019)
On a sunny dock in Gibraltar, Slaton returns to the sailboat he shares with his wife and young son to find them missing. The only clue to their whereabouts is a cryptic message: If he wants to see them again, he must eliminate an obscure scientist working for the International Atomic Energy Agency. Slaton races to Vienna to unravel the scheme. Half a world away, a small team of ISIS operatives arrives in North Korea. It is comprised of two suicidal jihadists, one technician, and the caliphate<U+2019>s only officer with naval experience. Their mission: to reestablish the group<U+2019>s relevance by undertaking a shocking strike against America. From Europe to North Korea to the Pacific Ocean, Slaton finds himself entangled in a deadly nuclear game. Working against him are a band of suicidal terrorists, supported by a North Korean government that is about to implode. That slate of actors, however, face something even more lethal. A devoted father and husband<U+2015>one who happens to be the perfect assassin.